AGRONOMIC EVALUATION OF GRAFTED BITTER GOURD (MOMORDICA CHARANTIA L.) CULTIVARS FOR GROWTH AND YIELD - N. A. TAMILSELVI; L. PUGALENDHI (The Bioscan, 2015)
The experiment was conducted during the year 2012-13 to study the effect of cucurbitaceous rootstocks on bitter gourd growth and yield (Momordica charantia L.) by comparing grafted bitter gourd plants with non-grafted plants under field conditions. The bitter gourd cultivars viz., Palee F1 and CO 1 were grafted on to two cucurbit rootstocks viz., pumpkin (Cucurbita moschata) and sponge gourd (Luffa cylindrica). The grafting method adopted in this study was side grafting. The result revealed that the grafted plants had better vegetative growth and yield than the non-grafted plants (check). Highest vegetative growth (856.66 cm), least node number to first female flower appearance (25.80), narrow sex ratio (17.8) and fruit number (28.02 fruits ) and fruit yield per vine (3.55 kg/vine) were observed in Palee F1 scion grafted onto ‘pumpkin (Cucurbita moschata)’ rootstock than other graft combinations and non-grafted plants. The differences recorded for growth and yield of the tested cultivars might be due to different growth characteristics, graft affinity and compatibility. This evidence indicates that grafting bitter gourd scions onto specific rootstock significantly influences growth and yield without deterioration in the fruit quality.